DNA damage and transcription stress cause ATP-mediated redesign of metabolism and potentiation of anti-oxidant buffering (2019)
Accumulation of DNA lesions causing transcription stress is associated with natural and accelerated aging and culminates with profound metabolic alterations. Our understanding of the mechanisms governing metabolic redesign upon genomic instability, however, is highly rudimentary. Using Ercc1-defective mice and Xpg knock-out mice, we demonstrate that combined defects in transcription-coupled DNA repair (TCR) and in nucleotide excision repair (NER) directly affect bioenergetics due to declined transcription, leading to increased ATP levels. This in turn inhibits glycolysis allosterically and favors glucose rerouting through the pentose phosphate shunt, eventually enhancing production of NADPH-reducing equivalents. In NER/TCR-defective mutants, augmented NADPH is not counterbalanced by increased production of pro-oxidants and thus pentose phosphate potentiation culminates in an over-reduced redox state. Skin fibroblasts from the TCR disease Cockayne syndrome confirm results in animal models. Overall, these findings unravel a mechanism connecting DNA damage and transcriptional stress to metabolic redesign and protective antioxidant defenses. © 2019, The Author(s).